The twins' family Christmas - McClain, Lee Tobin (Love inspired., 2018)
"Pastor Carson Blair plans a quiet Christmas vacation for his twin girlsuntil veteran Lily Watkins gets snowed in with them. Lily is drawn to the warmth of this family, but shes hiding a secret about Carsons late wife that threatens more than their holiday. And the twins have their own planone that includes a gift-wrapped mommy to complete their family."--